KONSEPSI SEMANGAT KEWIRAUSAHAAN CIPUTRA (Kesesuaian dengan Konsep Ekonomi Islam) - Wadhan Wadhan (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2016)
The objective of the research is about to identify the suitability between the entrepreneurship spirit concept of Ciputra and entrepreneurship spirit concept of Islamic economy. This is a library research that is directed to trace available literatures from any conventional and online libraries. The result of the research suggests that there is suitability between the entrepreneurship spirit concept of Ciputra and entrepreneurship spirit concept of Islamic economy. Mr. Ciputra is an entrepreneur. He is dare to take take any risks, able to survive in uncertainties, creative in managing ideas, has tough ambitions to record his achievements in the fields of business, art, and education. Instead, Mr. Ci has known as a person who never stops from working and learning to create valuable things. He does not feel shy to learn from someone else and be thankful for that. He believes in the hand of God to rum his business. Moreover, in the perspective of Islamic economy every legal effort of business must be relied on the blessing of Allah Ta’ala. That must be the philosophy of life of most Muslims to do business, to negotiate, and to transact, their heart must be engaged to the noble philosophy. Besides, attitude and behavior must be placed in the highest level in structure of Islamic economy design. It refers to honesty, trust, tolerant, promise keeping, faith in fate, bless of Allah, thankful, dedication, and syariah holder.